ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI SAWI HIJAU DI DESA NYANGGELAN KABUPATEN KLUNGKUNG - Nugraha, I Komang Agus Rai; Karmini, Ni Luh (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2020)
The growth of the agricultural sector is strongly influenced by the level of farmer's income. If the greater the income, it will show an influence on the factors of high income or input. The purpose of this study 1) To analyze the effect of capital, land area and price simultaneously on the income of green mustard farmers in Nyanggelan Village, Klungkung Regency. 2) To analyze the effect of capital, land area and price partially on the income of green mustard farmers in Nyanggelan Village, Klungkung Regency. The data used in this study are primary data, namely by distributing questionnaires to green mustard farmers in Nyanggelan Village. The sample used in this study were 60 mustard greens farmers in Nyanggelan Village. The sample technique used is saturated sample. Using multiple linear regression analysis techniques. The results showed that the capital, land area, and price simultaneously had a significant effect on farmers' income. Capital partially has a significant effect on farmers 'income, land area partially has a significant effect on farmers' income. Price partially has a significant effect on farmers' income. The variable that most influences production is land area. Keywords: Capital, Land Area, Price, Income